Fat blockage and improved characteristics of Coated-Cassava chips using natural edible coating from carboxymethyl cellulose in Deep-Frying process. (2020) - Hashim, Liyana; Mat Ropi, Anis Alysha; Alikasturi, Amin Safwan; Anuar, Mohd. Razealy; Safiei, Nor Zanariah; Muhamad, Ida Idayu; Mohd Jusoh, Yanti Maslina; Shaharuddin, Shahrulzaman
Abstract: Production of the deep-fried cassava chips has contributed to high cooking oil waste production. The frying process could increases the lipid content and reduce the physical attributes of the chips. This research aimed to evaluate the effect of carboxymethyl cellulose (CMC) concentration (1, 2 and 3%) on the coated-fried cassava chips characteristics. A dipping-coating method was used and the characteristics evaluated were lipids content, colour measurement, texture, functional group and sensory analysis. All data were analysed using one-way ANOVA and Duncan multiple range test. Result showed 3% CMC could reduce the lipid content of chips up to 10%. Besides, the coated chips produced a better crispiness level as compared to uncoated chips. The colours were darker in the higher concentrations of CMC coated chips. FTIR spectra confirmed the presence of CMC coating on the coated sample. The coated chips showed a slightly higher sensory overall acceptability. Overall, the CMC-coated cassava chips reduced the lipid contents and improved physical properties of the snack.